Identifying Pedagogical Gaps and Opportunities to Strengthen HOTS through Digital Science Learning Media - Ida Rosdiyanti; Sulistyo Saputro; Harlita (LPPM Undiksha, 2025)
The low ability of Higher-Order Thinking Skills (HOTS) of Indonesian students based on consistently low PISA scores, amidst the demands of the Independent Curriculum which emphasizes the integration of 21st-century skills such as critical thinking, creativity, and digital literacy. This study aims to identify the needs of teachers and students for the development of e-modules based on contextual and interactive Problem-Based Learning (PBL). This type of research is descriptive study using a mixed methods approach, which integrates qualitative and quantitative methods. The research method used a mixed-method descriptive approach through classroom observation, semi-structured interviews with three science teachers, and questionnaire distribution to 86 eighth-grade junior high school students. The research instrument was validated with Aiken's V (0.867) and Cronbach's Alpha reliability (0.874). The results showed that 68.6% of students had difficulty understanding abstract concepts, teachers faced time and ICT competency constraints, and there was a high preference for interactive e-modules containing animations, simulations, and HOTS exercises. The novelty of this research lies in the needs analysis that integrates pedagogical, digital, and contextual dimensions in the development of PBL-based e-modules for junior high school level, which has previously been rarely studied in the context of Indonesian science education. The implications of this research emphasize that digital media integration not only functions as a means of conveying information, but also as a strategic tool to stimulate students' critical thinking, creativity, and problem-solving abilities.